What Are the Implications for Global Value Chains When the Market Shifts from the North to the South? - Kaplinsky, Raphael; Farooki, Masuma (World Bank, Washington, DC, 2014)
Rapid growth in many low-income economies was fuelled by the insertion of producers into global value chains feeding into high-income northern markets. This paper charts the evolution of financial and economic crisis in the global economy and argues that the likely outcome will be sustained growth in the two very large Asian Driver economies of China and India and stagnation in the historically dominant northern economies. Given the nature of demand in low-income southern economies, it is likely to be reflected in sustained demand for commodities, with other southern economy producers in global value chains being forced into lower levels of value added. Standards are likely to be of considerably reduced significance in value chains feeding into China and India.